INDONESIAN TO ENGLISH USAGE IN HOSPITALITY STAFF COMMUNICATION: A LINGUISTIC INTERFERENCE ANALYSIS - Achmad Leofaragusta Kurniawan Komerendo; Ridayani Ridayani; Fadilaturrahmah Fadilaturrahmah; Marsinah Marsinah; M. Bambang Purwanto (Wiralodra English Journal, 2025)
This study aims to analyze the interference of the Indonesian language with the use of English by hotel and restaurant staff in the tourist area of Jakabaring Sport Center, Palembang. The focus of the study includes grammatical and phonological interference patterns influenced by the use of regional languages, especially the Palembang dialect, in professional communication. The results showed that interference occurred significantly, with four main points of word selection inference, phonological interference, grammatical inference, and cause of inference. The discussion identified that the leading causes of interference were the lack of formal training, the dominance of regional languages, and the lack of a work environment that supports English language practice. These findings highlight the importance of locally-based English training design to improve staff communication competencies. The study concluded that language interference can be minimized through continuous training and the integration of learning technologies, ultimately improving the service quality of the hospitality and restaurant sectors.